Efeito do plasma rico em uréia na apoptose de neutrófilos de cães - Trinconi, Cristiana de Melo [UNESP]; Trevelin, Silvia Cellone; Barbosa, Tatiana Sousa [UNESP]; Ciarlini, Paulo César [UNESP] (My University, 2011)
The acceleration of neutrophil apoptosis in human patients with kidney disease and its relationship with the uremic toxins have been, in recent years, widely investigated due to its importance as an immunosuppressant. Chronic renal failure (CRF) is the most common nephropathy observed in dogs, however, there are no reports in the literature about the effect of uremia in the apoptosis for this species. Considering that urea is the most routinely uremic toxin measured in the CRF clinic addressing, it is proposed to test the hypothesis that urea is able to change the morphology of dog’s neutrophils and to accelerate their programmed cell death and that this effect is dependent on the time of exposure. Blood plasma of ten healthy dogs was replaced by homologue plasma enriched with two different concentrations of urea (114.6 and 62.9 mmol/L) and incubated at 37ºC for four hours. The concentration of urea was determined by UV enzimatic method and the apoptotic index evaluated by morphometry. The rate of apoptotic neutrophils increased after two and four hours of incubation (p<0.05), regardless of the addition of urea. The apoptotic index of neutrophils incubated with plasma rich in urea was higher than those containing non-enriched plasma, but this difference was not significant. In conclusion, the increase of plasmatic urea concentration “ex vivo” alone does not promote the acceleration of dog’s neutrophils apoptosis. It is possible that the “in vivo” immunossupresor effect of urea, is similar to that observed in humans, where it is also associated with other mecanisms and in synergism with others toxins.

La aceleración de la apoptosis de los neutrófilos en pacientes humanos nefrópatas y su relación con las toxinas urémicas han sido en los últimos años ampliamente investigadas debido su importancia como elemento inmunosupresor. La insuficiencia renal cronica (IRC) es la nefropatía más común observada en perros, mientras tanto, no hay relatos de literatura en cuanto al efecto de la uremia en la apoptosis para esta especie. Considerando que la urea es la toxina más rutinariamente cuantificada abordando en el diagnóstico de IRC, se propone probar la hipótesis de que la urea es capaz de alterar la morfología de los neutrófilos de perros y acelerar su proceso de muerte celular programada y que este efecto es dependiente del tiempo de exposición. Para esto, el plasma sanguíneo de diez perros sanos fue substituido por plasma homólogo enriquecido con dos diferentes concentraciones de urea (114,6 e 62,9 mmol/L) e incubado a 37°C, por cuatro horas. La concentración de urea fue determinada por el método enzimático UV y el índice apoptótico fue determinado por morfometría. La taza de neutrófilos apoptóticos aumentó después de dos a cuatro horas de incubación (p<0,05), independientemente de la adición de urea. El índice apoptótico de neutrófilos incubados con plasma rico en urea fue mayor de aquellas con plasma no enriquecido, por tanto tal diferencia no fue significativa. Se concluye que el aumento de la concentración de urea plasmática "in vivo" aisladamente no promueve la aceleración de la apoptosis de neutrofilos de perros. Es posible que el efecto inmunosupresor "in vivo" de la urea es semejante a lo que ocurre en humanos, donde está asociado a otros mecanismos y en sinergismo con otras toxinas urémicas.

A aceleração da apoptose dos neutrófilos em pacientes humanos nefropatas e sua relação com as toxinas urêmicas têm sido, nos últimos anos, amplamente investigada devido sua importância como elemento imunossupressor. A insuficiência renal crônica (IRC) é a nefropatia mais comum observada em cães, no entanto, não há relatos na literatura quanto ao efeito da uremia na apoptose para esta espécie. Considerando que a uréia é a toxina mais rotineiramente quantificada na abordagem clínica da IRC, propõe-se testar a hipótese de que a uréia é capaz de alterar a morfologia dos neutrófilos de cães e acelerar seu processo de morte celular programada e que este efeito é dependente do tempo de exposição. Para tal, plasma sangüíneo de dez cães sadios foi substituído por plasma homólogo enriquecido com duas diferentes concentrações de uréia (114,6 e 62,9 mmol/L) e incubado a 37o C por quatros horas. A concentração de uréia foi determinada pelo método enzimático UV e o índice apoptótico por morfometria. A taxa de neutrófilos apoptóticos aumentou após duas e quatro horas de incubação (p<0,05), independente da adição de uréia. O índice apoptótico de neutrófilos incubados com plasma rico em uréia foi maior do que aquelas com plasma não enriquecido, entretanto tal diferença não foi significativa. Conclui-se que o aumento da concentração de uréia plasmática “ex vivo” isoladamente não promove a aceleração da apoptose de neutrófilos de cães. É possível que o efeito imunossupressor da uréia “in vivo”, à semelhança do que ocorre em humanos, também está associado a outros mecanismos e em sinergismo com outras toxinas urêmicas.
Effect of rich urea plasma in apoptosis of neutrophils in dogs
Efecto del plasma rico en urea en la apoptosis de neutrófilos de perros
Keywords: Programmed cell death; Uremic toxin; Polymorphonuclear; Leukocyte dysfunction; Muerte celular programada; Toxina urémica; Uremia; Polimorfonuclear; Disfunción leucocitaria; Morte celular programada; Toxina urêmica; Uremia; Polimorfonuclear; Disfunção leucocitária